Self-Harm in Eating Disorders (SHINE): a mixed-methods exploratory study - Maria Michail; Helen Bould; Anna Lavis; Sheryllin McNeil; Anthony Winston; Kalen Reid; Christina L Easter; Rosina Pendrous (BMJ Open)
Introduction Self-harm is highly prevalent among young people with eating disorders. However, why a young person may develop and continue to experience both an eating disorder and self-harm is unclear. This study will investigate the frequency, intensity, duration, function, context and processes of self-harm among people aged 16–25 diagnosed with an eating disorder. It will explore participants’ perspectives on the genesis and functions of both their self-harm and eating disorder, as well as their support needs. The study was designed with the input of members of a Young Persons’ Advisory Group, who will be key to study delivery and dissemination.Methods and analysis This exploratory study has a sequential mixed-methods explanatory design. Between 70 and 100 young people aged 16–25 with both an eating disorder diagnosis and self-harm thoughts and/or behaviours will be recruited from three NHS Eating Disorder outpatient services in England. Phase 1: a 14-day (six prompts per day) ecological momentary assessment (EMA) of participants’ feelings, thoughts, motivations, behaviours and experiences of self-harm. Phase 2: 20–30 participants from phase 1 will be reapproached to take part in an in-depth qualitative interview on the psychological, emotional and social factors that underlie their self-harm and eating disorder as well as their support needs. EMA data from phase 1 will be analysed using descriptive and multilevel statistics. Qualitative interview data from phase 2 will be analysed using inductive and deductive thematic analysis. Results from both phases will be integrated using a mixed-methods matrix, with each participant’s data from both phases compared alongside comparative analysis of the datasets as a whole.Ethics and dissemination The study gained ethical approval from the NHS HRA West Midlands–Black Country Research Ethics Committee (number: 296032). We anticipate disseminating findings to clinical, academic and lived experience audiences, at academic conferences, through peer-reviewed articles, and through various public engagement activities (eg, infographics, podcasts).